Proposing construct for organizational agility model in Malaysian automotive organization - Hassan, N.H. (IEEE Computer Society, 2019)
In recent Malaysia economic growth, manufacturing is one of stated industry that contributed high source of income for the country. Automotive industry is one of widely manufacturing category discussed by researchers due to its importance. Malaysia automotive organizations play important roles in representing Malaysian products and technologies. In achieving Industrial Revolution 4.0 it is really imperative for automotive organizations to be highly competitive by be responsive to their stakeholders. This research-in-progress investigates how, Information Technology Infrastructure Flexibility (ITIF), Learning orientation (LO), and organizational Agility (OA) are related. In obtaining the answer, this paper mainly discussed on how the constructs and items are identified, how reflective, formative or mixed construct is determined. These phases are important to quantitative research in order to avoid wrong specification of measurement model. This followed by empirical findings for all hypotheses. Empirical test for reflective and formative construct are using SmartPLS 3. The proposed model will assist IT and business managers to improve information technology infrastructure, develop learning programs, staff development, as well as responsive initiatives for organization. Â© 2019 IEEE.